Generalized and Improved (G′/G)-Expansion Method for (3+1)-Dimensional Modified KdV-Zakharov-Kuznetsev Equation - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali (© 2013 PLoS ONE, 2016)
This article was published in the PLoS ONE [© 2013 Naher et al.] and the definite version is available at :http://dx.doi.org/10.1371/journal.pone.0064618 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0064618